Changes in the living conditions of the Cracovian Roma after Polish accession to the EU = Zmiany w sytuacji bytowej krakowskich Romów po wejściu Polski do Unii Europejskiej - Żurek, Robert (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The core of analysis in this article is the situation of the Cracovian Roma community after Polish accession to the European Union. The analysis considers two levels - institutional (activity of Roma associations) and private (the situation of families and individuals). The base material in the case of institutions are interviews with their representatives and, in the case of individuals, interviews by questionnaires.
Keywords: Roma; ethnic minority; social position; discrimination; Romowie; mniejszość etniczna; pozycja społeczna; dyskryminacja